Early identifiation of specific dyslexia syndrome in children with neurological diseases - Τζούφη Μερόπη; Ζακοπούλου Βικτώρια; Βέρμπη Χάιδω; Νάκου Ηλιάδα; Μαυρέας Βενετσιάνος; Σιαμοπούλου-Μαυρίδου Αντιγόνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF